From seed security to food security: validating ‘Triple S’ seed conservation technology in new contexts. - Cherinet, M.; Gashawbeza, D. (International Potato Center, 2015)
This flyer outlines the progress made between 2014 and 2015 regarding the validation of Triple S (Storage in Sand and Sprouting) technology in the Southern Nations Nationalities and Peoples’ Region (SNNPR) Ethiopia.